1996
DOI: 10.1149/1.1837184
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of Boron in LiF‐NaF‐KF‐ Melts

Abstract: ABSTRACT.The electrochemical reduction of B(III) to 8(0) in KBF4-LiF-NaF-KF melts has been studied by voltammetric and chronopotentiometric methods. Glassy carbon, Pt, and Ag were used as working electrode materials. Only in the case of Ag was the reduction not complicated by interaction between boron and the electrode material. On a silver electrode 8(111) was reduced to B(0) in a single irreversible step in the KBF4 concentration range up to 5.7 X 10 mole percent (mb). The cathodic half-wave potential was -1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…In the works [7][8][9][10] the electrochemical behavior of boron, the laws of electrode processes at its refining, the solubility of boron compounds in molten alkali metal chlorides are studied. In literature the processes of joint electroreduction cerium and boron ions in halide melts on a tungsten electrode are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In the works [7][8][9][10] the electrochemical behavior of boron, the laws of electrode processes at its refining, the solubility of boron compounds in molten alkali metal chlorides are studied. In literature the processes of joint electroreduction cerium and boron ions in halide melts on a tungsten electrode are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…And, for LiFKFB 2 O 3 melts, B 2 O 3 firstly reacted with LiFKF to form KBF 4 , which was then reduced to element boron according to Eqn . In addition, Polyakova et al . found that the electrochemical reduction of B(III) to B(0) on a sliver electrode in the KBF 4 LiFNaFKF melts depended on the concentration of KBF 4 .…”
Section: Electrolytic Production Of Elemental Boronmentioning
confidence: 99%
“…/ is cathodic half-peak potential), is larger than the value required for the reversible process of formation of an insoluble substance ( (0.071/n)*V at 1073 K where, n is the number of electrons transferred for the reduction process) [33,34], indicating that the reduction of boron species on platinum electrode from KCl-KF-NaBF 4 melt is not reversible. (Fig.…”
Section: Cyclic Voltammetrymentioning
confidence: 99%
“…Polyakova et al [34] reported that the broadening of the cathodic peak in CV occurred due to the ohmic control of deposition of boron. These authors presented linear plots of peak current and peak potentials against the square root of scan rate and concluded that a surface boron film formed on the electrode rendered the process to be controlled by ohmic resistance.…”
Section: Apparent Surface Resistancementioning
confidence: 99%
See 1 more Smart Citation